Biological aspects of squid (Loligo edulis) in the waters of Eastern North Sumatra, Indonesia - Dadan Zulkifli; Ratna Suharti; Yuni Fast Track Anjeli Sihombing; Meuthia Aula Jabbar; Siti Mira Rahayu; Aditya Bramana; Hendra Irawan; Deni Aulia (Depik, 2023)
Squid is one of the non-fish resources that have economic value and is a target species in demersal fisheries activities with squid fishing gear and stick-held deep net. This research aims to determine the biological aspects of squid (Loligo edulis) such as length frequency distribution, length-weight relationship, sex ratio, gonadal maturity level, gonadal maturity index, size at first caught, and size at first maturity of the gonads. The method used in this research was a descriptive survey. The sample collection method used systematic random sampling and purposive sampling techniques. This observation was carried out on March 7 to July 30, 2022, at the Belawan Ocean Fishing Port and Tanjung Balai Port. The results showed that the average length distribution of squid was 17.73 cm. The relationship between the length and weight of squid is negative allometric. The sex ratio is 1:1.05. The negative allometric growth pattern is dominated by Gonadal Maturity Level (GML) I and GML II. The highest GML value for male squid was 2.06% at GML III, and the highest GML value for female squid was 1.92% at GML III. The average size of the caught squid length (Lc) is 10.42 cm. The size of the first gonad maturity (Lc) was 13.32 cm.Keywords:SquidBiological aspectsFisheries aspectManagement effort